LEGAL ASPECTS OF BUSINESS COMPETITION ON ELECTRONIC COMMERCE - Dian Herlambang; Dodi Yudo Setyawan (Prosiding International conference on Information Technology and Business (ICITB), 2018)
In Indonesia, electronic commerce can be said to be very developed. In 2007 there was a case which can be said to be the first case of electronic commerce. The data can be seen based on studies and suggestion that was carried out by the Business Competition Supervisory Commission (KPPU) on the case of the MoU between the Government of Indonesia and Microsoft (KPPU Report, 2007). This study was written to determine the implementation of the rules of business competition law and the policy of the KPPU in the field of business competition in relation to electronic commerce. In this study two approaches were used, namely the normative approach. The data in this study are mainly obtained from library research, especially on primary legal materials in the field of business competition. The data analysis used is qualitative method. This is closely related to research which can be categorized by normative legal research that approach is more abstract-theoretical. the results of the study show that the e-commerce business sector still does not lead to anti-business competition practices even though it still enters the surveillance radar. This may be due to electronic commerce itself is a new form of trade.Keywords : E-commerce, Business Competition, and Policy